Asylum - Roux, Madeleine, 1985- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2013)
"Three teens at a summer program for gifted students uncover shocking secets in the sanatorium-turned-dorm where they're staying--secrets that link them all to the asylum's dark past"--
Sequel: Sanctum.
Keywords: Supernatural -- Fiction; Universities and colleges -- Fiction; Mental illness -- Fiction; Haunted places -- Fiction; Psychiatric hospitals -- Fiction; Ability -- Fiction; Mystery and detective stories; JUVENILE FICTION / Horror & Ghost Stories; JUVENILE FICTION / Mysteries & Detective Stories; JUVENILE FICTION / Social Issues / New Experience; Fiction